Gurun Pottery Sdn Bhd - Yeoh, Chin Hoe (1997)
Ourun Pottery Sdn. Bhd. (OP) was a wholly owned subsidiary of Hull Trading Sdn Bhd (HT). It was a ceramic manufacturer in sanitary wares. The factory waS situated in Gurun, Kedah and it occupied two acres of land with a built-up factory floor of about 1.0 acre. The main items of sanitarywares manufactured by OP were sitting pan (pedestal), squatting pan, wash basin, urinal bowl and soap holder. The parent company, HT, was concerned that Opts production output had declined from 109,938 units in 1995 to 100,420 units in 1996. Likewise, profit before tax also showed a downward trend from RMI03k in 1995 to RM65k in 1996. The situation was aggravated when OP could not produce enough stocks for the marketing division of HT to distribute to its customers. It was reported that the delay in deliveries on the part of OP had resulted in orders being canceled by the customers. The Managers complained that the image of OP products was deteriorating in the market, and HT being distributor for OP also suffered the loss in revenue. The Executive Director of HT, Mr Ting Chew Jin, commented that if GP failed to restore to the required efficient production and healthy profitability, then it would not survive due to the keen competitions in the sanitaryware industry. Mr Ting also sat in GP Board and primarily responsible for the performance of GP.